Penatalaksanaan Fisioterapi Pada Kasus Hernia Nucleus Pulposus Lumbal 3 - 5 Dan Sacrum 1 Di RSUD Sukoharjo - Anshari, Riyadi; , Totok Budi S, S.Fis., MPH (2016)
Background: Herniated Nucleus Polposus (HNP) is a condition caused by the protrusion of the nucleus pulposus of discus into the ring along with the emphasis on the roots the nerve roots. Interventions that can be used in cases HNP is Transcutaneous Electrical Nerve Stimulation (TENS) and Mc.kenzie Exercise. Purpose: To determine the mechanism of Transcutaneous Electrical Nerve Stimulation (TENS) can reduce pain in cases of Herniated Nucleus Polposus (HNP) and to find a form of exercise Mc.kenzie Exercise in the case of Herniated Nucleus Polposus (HNP). Method: case study carried out six times he therapy. To assess changes in pain by Verbal Describe Scale (VDS), muscle strength with Manual Muscle Testing (MMT) and functional activity with Owestry scale. Result: After the therapy is conducted six times. The result is decrease pain with Verbal Describe Scale (VDS), pain silence from T0: one be T6: zero tenderness from T0: four be T6: zero, pain motion from T0: six be T6: one. Decrease Owestry Scale from T0: 22 be T6: 10. Nothing increase iin muscle strength with Mmaual Muscle Test (MMT), flexor hip from T0: four be T6: four, extensor hip from T0: four be T6: four, abductor hip from T0: four be T6: four, adductor hip from T0: four be T6: four, abdominal from T0: four be T6: four, and trunk from T0: four be T6: four. Conclusion: After therapy with Transcutaneus Electrical Nerve Stimulation (TENS) modalities and McKenzie Exercise therapy six times, decrease pain silent, press and movement. An increase in the functional activity. Nothing increase in muscle strength. Keywords: Herniated Nucleus Pulposus (HNP), Transcutaneus Electrical Nerve Stimulation (TENS), McKenzie Exercise, Verbal Describe Scale (VDS), and Manual Muscle Test (MMT).